Letters from the Front and Memoires in a Museum Exhibition as the Means of Commemoration and Formation of Historical Memory - Nochvina, Bella A. (2021)
The article researches the process of historical memory formation and the role of museum spaces in it. The authors consider the use of letters from the front as the means of commemoration. The issues of commemoration and re-commemoration, museum reflection and its influence on historical memory are studied. Special attention is paid to museumification of front letters and memoires of war workers. The authors consider the new possibilities of using them in museum displays using multimedia technologies, emphasizing the higher accessibility of the letters’ content in multimedia. The research novelty consists in the cross-disciplinary view of a historical source through the prism of museum space. The authors show the properties and possibilities of narrative sources which are now available due to modern technologies. The unpublished ego-documents (private letters and memoires) from museum funds were studied and described. The research topicality is due to identification of the influence of written museum exhibits on the formation and socialization of historical memory. It is proved that the personal materials in a museum display using modern technical opportunities enhance the informative effect, stimulating commemoration and facilitating the formation of historical memory. The article employs the experience of fund, exhibition and excursion work of the Museum of the history of Gorky railroad development.